El México rojo: Entropic Humour, Naturalism, and Death in Luis Buñuel’s El río y la muerte and Ensayo de un crimen - Kenny, Ivan (Revista Canadiense de Estudios Hispánicos, 2022)
This article analyzes death, violence, and machismo in two Mexican films by Luis Buñuel, El río y la muerte (1954) and Ensayo de un crimen (1955), starting from a naturalist perspective (Deleuze, 1986) and applying the concept of “entropic” humour (O’Neill, 1990). Despite numerous studies on surrealist humour in Buñuel’s films, it is necessary to investigate how his “peculiar” black humour operates, both in his naturalist works and in a Mexican context, “the chosen land of black humour” (Breton, 1941). I contend that both films satirically link violent impulses and stereotypical cultural constructions surrounding death in Mexico.